Companies as local skill-providers? The ‘skills ecosystem’ in Mexico - Fuchs, Martina; Röhrer, Natascha; Vogelsang, Beke (ERDKUNDE, 2021)
A focus of economic geography is on how actors promote the local knowledge base. Studies usually show that companies act as recipients of locally generated knowledge, and not as producers of knowlege. Recruiting graduates of local vocational schools and universities enables the companies to play this role. However, companies sometimes also act as providers of knowledge, in the sense that they offer apprenticeships or comprehensive internships for pupils and students. This article focuses on this interface of ‘dual’ actvities, which connect the companies with vocational schools and universities. Recently, the concept of the skills ecosystem, which addresses this interface within the local actor network, has become popular. Starting with this concept and embedding it into the debate of economic geography, this contribution focusses on Mexico and investigates how the local actors integrate companies in dual activities. Based on qualitative methods, the study illustrates that there is a two-part skills ecosystem in Mexico’s Central Highland. The smaller part consists of dual vocational education and training and is found in the technological ‘high-road’ part of the economy. The other part mainly comprises low-tech and mostly smaller companies that do not engage in dual practices. The conclusion discusses the contribution of a skills ecosystems-approach to future research.